2009
DOI: 10.1007/s11664-009-0904-2
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Silver Alloy for Advanced Barrierless Metallization

Abstract: In this study we observed significantly improved properties, over a pure copper (Cu) film, for a copper-silver alloy film made with a pure copper film co-sputtered with a minute amount of either Ag 0.3 N 0.4 or Ag 1.2 N 0.7 on a barrierless Si substrate. In either case, no noticeable interaction between the film and the Si substrate was found after annealing at 600°C for 1 h. The Cu(Ag 0.3 ,N 0.4 ) film was thermally stable after annealing at 400°C for 240 h. The film's resistivity was $2.2 lX cm after anneali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The thermal stability of the Cu(RuHfN x ) film was better than that of the Cu(HfN x ) film, as indicated by resistivities of 2.4 lX cm after annealing for 200 h and 2.9 lX cm after annealing for 180 h. Our previous study 4 found that a Cu(W 2.8 ) film subjected to annealing at 400°C for 48 h had a resistivity of 4.6 lX cm and that a Cu(Ag 0.3 ,N 0.4 ) film annealed at 240 h had a resistivity of 2.6 lX cm. 7 In comparison, the resistivity of the Cu(RuHfN x ) film described in the present study indicates that it had a suitable thermal reliability. Barmak et al 8 studied 620-nmthick films prepared using 0.35 at.% Hf and found that the films had resistivities of 4.5 lX cm after they were annealed at 400°C for 5 h. In this study, the Cu(HfN x ) and Cu(RuHfN x ) films were found to have resistivities of 3.46 lX cm and 3.32 lX cm, respectively, after they were annealed for 1 h, which is comparable to the results obtained by Barmak et al 8 The resistivity of the Cu(RuHfN x ) alloy film after annealing at a high temperature of 720°C and at 400°C for 240 h lies between 2.4 lX cm and 2.6 lX cm.…”
Section: Resistivity Results Of Cu(ruhfn X ) Alloy Filmssupporting
confidence: 51%
“…The thermal stability of the Cu(RuHfN x ) film was better than that of the Cu(HfN x ) film, as indicated by resistivities of 2.4 lX cm after annealing for 200 h and 2.9 lX cm after annealing for 180 h. Our previous study 4 found that a Cu(W 2.8 ) film subjected to annealing at 400°C for 48 h had a resistivity of 4.6 lX cm and that a Cu(Ag 0.3 ,N 0.4 ) film annealed at 240 h had a resistivity of 2.6 lX cm. 7 In comparison, the resistivity of the Cu(RuHfN x ) film described in the present study indicates that it had a suitable thermal reliability. Barmak et al 8 studied 620-nmthick films prepared using 0.35 at.% Hf and found that the films had resistivities of 4.5 lX cm after they were annealed at 400°C for 5 h. In this study, the Cu(HfN x ) and Cu(RuHfN x ) films were found to have resistivities of 3.46 lX cm and 3.32 lX cm, respectively, after they were annealed for 1 h, which is comparable to the results obtained by Barmak et al 8 The resistivity of the Cu(RuHfN x ) alloy film after annealing at a high temperature of 720°C and at 400°C for 240 h lies between 2.4 lX cm and 2.6 lX cm.…”
Section: Resistivity Results Of Cu(ruhfn X ) Alloy Filmssupporting
confidence: 51%
“…To realize this task, conductors made from copper alloy films with an increased thermal stability have been proposed. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In the alloy films we fabricated, we observe no noticeable interactions between the copper interconnect and the barrier-free silicon substrate after annealing at 680 C for 1 h. 17) We anticipate to apply these alloy films with such a low electric resistivity to making interconnects. Previously, we succeeded in introducing insoluble alloyed elements, such as refractory and transition metals (W, Mo, Ru, and Re), and their nitrides, in Cu interconnects.…”
Section: Introductionmentioning
confidence: 88%
“…The alloying of Cu with insoluble components has attracted the attraction of many researchers owing to its many for several industrial applications and is crucial in materials science. For example, Cu(RuN x ), films were developed and reported in 2007 and 2010; [5][6][7][8][9][10] previous studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have shown that Cu(ReN) 13) alloy films are thermally stable up to 730 °C. Iijima et al and Dixit et al developed Cu-Mn alloy films that can be applied to the fabrication of interconnects in semiconductor manufacture.…”
Section: Introductionmentioning
confidence: 99%